Dynamic general equilibrium modeling computational methods and applications - Heer, Burkhard 1967-; Maußner, Alfred (Springer, 2024)
Part I: Representative Agent Models: Basic Models -- Perturbation Methods: Framework and Tools -- Perturbation Methods: Solutions -- Perturbation Methods: Model Evaluation and Applications -- Weighted Residuals Methods -- Simulation-Based Methods -- Discrete State Space Value Function Iteration -- Part II: Heterogenous Agent Models: Computation of Stationary Distributions -- Dynamics of the Distribution Function -- Overlapping Generations Models with Perfect Foresight -- OLG Models with Uncertainty -- Part III: Numerical Methods: Linear Algebra -- Function Approximation -- Differentiation and Integration -- Nonlinear Equations and Optimization -- Difference Equations and Stochastic Processes.
Keywords: Verteilungstheorie; Wachstumstheorie; Stochastische dynamische Optimierung; Allgemeines Gleichgewichtsmodell; Konjunkturtheorie; Dynamische Makroökonomie; Economics; Econometrics.; Macroeconomics.; Economic development.; Computer science.